2023
DOI: 10.1002/cam4.5534
|View full text |Cite
|
Sign up to set email alerts
|

An immune, stroma, and epithelial–mesenchymal transition‐related signature for predicting recurrence and chemotherapy benefit in stage II–III colorectal cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A higher risk group had a worse prognosis compared to a low-risk group in this study. Prognostic risk models for different subgroups provide a basis for clinical translation [ 41 ]. Regarding the correlation between the risk model and clinical stage, a nomogram revealed that the combined utilization of both indicators resulted in a higher predictive performance (as determined by the ROC curve) than that of either parameter alone.…”
Section: Discussionmentioning
confidence: 99%
“…A higher risk group had a worse prognosis compared to a low-risk group in this study. Prognostic risk models for different subgroups provide a basis for clinical translation [ 41 ]. Regarding the correlation between the risk model and clinical stage, a nomogram revealed that the combined utilization of both indicators resulted in a higher predictive performance (as determined by the ROC curve) than that of either parameter alone.…”
Section: Discussionmentioning
confidence: 99%